The Catholic Case Against War : A Brief Guide. - Cochran, David Carroll (University of Notre Dame Press, 2024)
The Catholic Case against War demonstrates how the Catholic mantra "Never again war!" reflects a set of powerfully realistic teachings on war and peace. Over the last five decades, the Catholic Church has emerged as a powerful critic of war and as an advocate for its alternatives. At the same time, researchers of armed conflict have produced a considerable body of scholarship on war and its prevention. The Catholic Case against War compares these seemingly disparate lines of thought and finds a remarkable harmony between the two. Drawing on years of Vatican documents and papal statements, political scientist David Carroll Cochran clearly presents the key elements of the Church's case against war. Far from a naïve, optimistic call for peace, these teachings are consistent with the empirical research on the realities of contemporary warfare. The result is a look not only at the explicit moral case against war developed by the Vatican but also at its remarkable realism and relevance to world conflict today.
Description based upon print version of record.
Keywords: Catholic Church -- Peace.; Peace -- Religious aspects -- Catholic Church.; Nonviolence -- Religious aspects -- Catholic Church.; War -- Religious aspects -- Catholic Church.; Pacifism.; Religion and politics.; Paix -- Aspect religieux -- Église catholique.; Non-violence -- Aspect religieux -- Église catholique.; Pacifisme.; Religion et politique.; RELIGION / Christian Theology / Ethics